Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan 4C (Critical Thinking, Creativity, Communication Dan Collaboration): Studi Eksperimen Pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 2 Singaparna Tahun Ajaran 2024/2025 - Dina Andriani; Ai Nur Solihat; Ati Sadiah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This problem in this study is the low level of students' 4C skills in economics learning, as evidenced by the continued use of lecture-based teaching methods. This has led to students being less active during the learning process. The aim of this study is to determine the effect of the Problem Based Learning (PBL) model on students’ 4C skills (critical thinking, creativity, communication, and collaboration). The research method used in this study is a quasi-experimental design with a pretest-posttest control group design. The population in this study consisted of all 11th-grade students at SMAN 2 Singaparna in the 2024/2025 academic year. The sample used included class XI-7, consisting of 33 students as the control group, and class XI-8, consisting of 34 students as the experimental group, which was taught using the PBL model. The instruments used in this study were pretest-posttest assessments and observation sheets. The data analysis techniques used in this study included normality test, homogeneity test, paired sample t-test, Wilcoxon test, and Mann-Whitney test. The results of the data analysis showed a significance value of 0.000 < 0.005, indicating that H₀ is rejected and H₁ is accepted. This means that there is a significant improvement in the 4C skills of students who were taught using the Problem Based Learning model. The effectiveness of this improvement is evidenced by the N-Gain score of the experimental class, which was 0.74, indicating a high category. It can be concluded that the Problem Based Learning model has a significant effect on improving students’ 4C skills (critical thinking, creativity, communication, and collaboration) in economics learning for 11th-grade students at SMAN 2 Singaparna.